Characteristics and Needs of Psychiatric Patients with Prolonged Hospital Stay. (April 2015) - Aflalo, Marc; Soucy, Nathalie; Xue, Xiaoqing; Colacone, Antoinette; Jourdenais, Emmanuelle; Boivin, Jean-François
Objective: To describe the characteristics and needs prior to, on admission, during the first month in hospital, at the thirtieth day of hospitalization and posthospital discharge of psychiatric patients occupying acute beds. Methods: This prospective observational study was conducted in 2 tertiary care hospitals. Adult patients hospitalized on a psychiatric unit for 30 days were identified. Data was collected from their medical charts and interviews with their health care team. The categorization of acute and nonacute status at day 30 was based on the health care professional's evaluation. Descriptive and univariate analyses were performed. Results: A total of 262 patients were identified (mean age 45 years), 66% lived at home and 11% were homeless. More than one-half were cognitively impaired and a few had special medical needs. Ninety-seven per cent had been admitted from the emergency department. At day 30, 81% of patients required acute care, while 19% (95% CI 15% to 24%) occupied an acute care bed, despite the resolution of their acute condition. The main reason preventing discharge of nonacute patients was the difficulty or inability to find appropriate resources that met patients' needs. As for patients who required acute care, the most common psychiatric issues were delusions or hallucinations (34%), inability to take medications independently (23.6%), and inadequate control of aggression or impulsivity (16.5%). Conclusions: Prevention of the discharge of nonacute patients is largely due to the difficulty in finding appropriate resources that meet patients' needs. Improved access to community and subacute care resources could potentially facilitate the hospital discharge of psychiatric nonacute patients.